Evaluating and comparing geochemical sampling protocols in dinosaur eggshells - Coimbra, Rute (2023)
GeoBioTec Research Group (FCT – Fundação para a Ciência e Tecnologia, Portugal), by project PLEC2021-008203 project, funded by MCIN/AEI/10.13039/501100011033 and by the European Union “NextGenerationEU”/PRTR” , by Gobierno de Aragón [Group E18: Aragosaurus: Recursos Geológicos y Paleoambientales]; and by project PID2021-122612OB-I00; Spanish Ministry of Science and Innovation MCIN/AEI/10.13039/501100011033 and by the European Union “NextGenerationEU”/PRTR”,MCIN/AEI/10.13039/5011000110333. M. M-A is the recipient of a Ramon y Cajal contract RYC2021-034473-I. C. N.-L. is the recipient of a Juan de la Cierva-Formación contract FJC2020-044561-I, supported by the MCIN co-financed by the NextGenerationEU/PRTR. Sylvia Riechelmann is thanked for support during geochemical analysis and Cristina Sequeira for assisting SEM analysis. We thank Marcos Aurell (University of Zaragoza- Spain), for providing a vector file of the geological sketch in Fig. S1F . Constructive comments by two anonymous reviewers and editorial guidance provided by Eduardo Koutsoukos are also acknowledged. Publisher Copyright: © 2023 The Author(s)